2020
DOI: 10.1177/1756287219889496
|View full text |Cite
|
Sign up to set email alerts
|

Same sized three-way indwelling urinary catheters from various manufacturers present different irrigation and drainage properties

Abstract: Background: The three-way indwelling urinary catheter (IUC) is used for continuous bladder irrigation and is considered the cornerstone for clinical treatment of patients with macroscopic hematuria. Although there seems to be a logical relationship between catheter size and efficacy of irrigation and drainage, we often observe relevant variations in these parameters between different brands of catheters available on the market. The aim of this study was to compare the mechanical properties of different models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
(20 reference statements)
1
2
1
Order By: Relevance
“…First, when the temperature of the irrigation fluid, bladder pressure, and height of the irrigation infusion set are held constant, the flow rate increases with the increasing diameter of the indwelling catheter. These results are consistent with previous findings 2 , 11 , 16 , 23 showing a positive relationship between catheter size and flow rate, which enables the effective elimination of urine, including thrombosis in the bladder. Based on the friction-adjusted Bernoulli's equation used in this study, the flow rate of the irrigation fluid entering the bladder is directly proportional to the diameter of the indwelling catheter.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…First, when the temperature of the irrigation fluid, bladder pressure, and height of the irrigation infusion set are held constant, the flow rate increases with the increasing diameter of the indwelling catheter. These results are consistent with previous findings 2 , 11 , 16 , 23 showing a positive relationship between catheter size and flow rate, which enables the effective elimination of urine, including thrombosis in the bladder. Based on the friction-adjusted Bernoulli's equation used in this study, the flow rate of the irrigation fluid entering the bladder is directly proportional to the diameter of the indwelling catheter.…”
Section: Discussionsupporting
confidence: 93%
“…These results align with Chang et al 12 , who observe a continuous increase in flow rate up to a height of 80 cm, but differ from their report of a decrease in infusion rate beyond that height. Notably, our study revealed that when the irrigation infusion set height matched that of the bladder or was below 10 cm, the irrigation fluid refluxed from the bladder towards the catheter, which was not reported in previous studies 9 , 11 , 24 . This discrepancy can be attributed to previous studies using model bladders and setting the bladder pressure to atmospheric pressure, instead of considering the actual bladder pressure in humans, when calculating or experimenting with bladder irrigation flow rate.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations